A new species of Atarphia (Coleoptera: Nitidulidae: Nitidulinae) from Laos - Gregson, Lily M.; Powell, Gareth S. (Zootaxa, 2024)
A new species of the genus Atarphia Reitter, 1884 is described from Phongsaly province, Laos. The new species, Atarphia mammutha sp. nov., is diagnosed from the three previously described members of the genus. An updated key to the species of Atarphia and additional distributional records are provided.